Examining Associations Between Psychopathic Traits and Executive Functions in Incarcerated Violent Offenders - Delfin, Carl; Andiné, Peter; Hofvander, Björn; Billstedt, Eva; Wallinius, Märta (Frontiers in Psychiatry, 2018)
Executive functions (EFs) are essential in almost all aspects of daily life and have been robustly related to antisocial behavior. However, the relationship between psychopathy and EFs has remained equivocal. Research investigating lower-level trait dimensions of psychopathy using standardized EF measures could be beneficial in addressing this issue. In this study, we examined associations between four EFs and four dimensions of psychopathic traits (interpersonal, affective, lifestyle, antisocial) using zero-order correlation and a combination of classical and Bayesian statistical methods. Two hundred and fourteen incarcerated male violent offenders were assessed with the Psychopathy Checklist-Revised and completed tests of cognitive flexibility, spatial working memory, response inhibition, and planning and problem-solving using the Cambridge Neuropsychological Test Automated Battery. Lifestyle psychopathic traits were significantly associated with reduced initial thinking time in a planning and problem-solving task, with a Bayes factor indicating substantial evidence for the observed correlation, and antisocial psychopathic traits showed a significant association with reduced initial thinking time in the same task, although the Bayes factor indicated only anecdotal evidence. Significant associations were also found between affective and antisocial psychopathic traits and less efficient strategic thinking in a spatial working memory task, and between affective, lifestyle and antisocial psychopathic traits and fewer problems solved in a planning and problem-solving task, although these findings were not corroborated by the Bayesian analysis. While the observed effects ranged between small and medium, our study suggests that reduced initial thinking times in planning and problem-solving is robustly associated with higher degrees of lifestyle and antisocial psychopathic traits.